Radio control of insects for biobotic domestication - Bozkurt, A.; Lal, A.; Gilmour, R. (2009 4th International IEEE/EMBS Conference on Neural Engineering, 2009)
In this paper, we demonstrate for the first time radio controlled stimulation of the neuromuscular system of the tobacco hawkmoth Manduca sexta to direct its flight. Silver and gold wire electrodes were implanted in the insect brain and thorax through Early Metamorphosis Insertion Technology, where a reliable mechanical attachment and electrical coupling was obtained with the insect tissue as a result of metamorphic growth. Super-regenerative receiver based architecture was used to receive transmitted signals from a remote controller to stimulate the insect, where the overall circuitry weighed only 650 milligrams and consumed 750 microwatts. Helium balloons were also used to assist the insect to lift an introduced weight. Flight initiation, stopping and controlled yaw were demonstrated on insects with remotely transmitted radio signals.